Biowaste valorization into valuable nanomaterials: Synthesis of green carbon nanodots and anode material for lithium-ion batteries from watermelon seeds - Ashraf, Humza; Karahan, Billur Deniz (Elsevier Ltd, 2024)
In this study, a solid biowaste watermelon seed is introduced for the first time as an alternative precursor for the production of fluorescent carbon nanodots and nanostructured activated carbon. Firstly, the seeds are carburized and then activated by using KOH after the ball milling process. The activated carbon is used as anode material in lithium-ion batteries and exhibits ?360 mAh g ? 1 capacity after the 200th cycle, with a coulombic efficiency of 98%. Additionally, carbon dots are fabricated by hydrothermally treating carburized seeds at different conditions. The obtained carbon dots show a remarkable fluorescence effect at 458 nm (when excited at 365 nm) and have the potential to be used in biomedical applications. The results show that by means of proper material selection and process design, low carbon footprint nanomaterials suitable for use in various applications can be synthesized successfully from organic wastes.
Keywords: Activated Carbon; Biowaste; Carbon Nanodots; Lithium-Ion Batteries; Waste to Wealth